Peran Serta Masyarakat di Kota Malang Berdasarkan UU No. 24 Tahun 1992 Dalam Pelaksanaan Otonomi Daerah - Harry, Musleh (ULUL ALBAB Jurnal Studi Islam, 2002)
People strongly urge for a civil society as the reflection of democracy in which their great participation determines the success of the government programs. The Constitutions No 2-1 1992 and No. 22 1999 show that people have the right to take a part in determining the programs. However, it is clearly seen that this civil right is not well accommodated As the result, the developmental programs are not designed to meet their needs and, even, create critical gaps. This social legal research is done to find out the effectiveness of application of the two above rules by paying more attention to the causes of the low participation given by the informal workers (PKL) and ways how the local government applies two rules. It turns out the government is not consistent in having law enforcement toward these people. This was caused by the fact that government considers these informal workers only have a temporal job. In addition, the government doesn’t have a definite policy as result of reform euphoria of Ulul Albab.